2008
DOI: 10.1128/jvi.00307-08
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Macaque TRIM5 Alleles Have Divergent Antiretroviral Specificities

Abstract: TRIM5␣ is a potent barrier to cross-species retroviral transmission, and TRIM5␣s from different species have divergent antiretroviral specificities. Multiple TRIM5 alleles circulate within rhesus macaque populations. Here we show that they too have different antiretroviral specificities, highlighting how TRIM5 genotypes contribute to protection in an individual or a population.TRIM5␣ is an important mediator of antiretroviral innate immunity in mammals and represents a significant barrier to zoonotic transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
66
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 32 publications
3
66
0
2
Order By: Relevance
“…S4), even though the L4/5 region of HIV CA is much longer than the corresponding region in MLV CA. An emerging consensus is that a conserved TRIM5α-binding mode exists for various viral capsids and that the surface details of the CA lattice dictate the species-specific interaction with TRIM5α (5,14,22,(41)(42)(43). On the other hand, TRIM5α possesses an intriguing curvature-independent pattern-recognition property.…”
Section: Discussionmentioning
confidence: 99%
“…S4), even though the L4/5 region of HIV CA is much longer than the corresponding region in MLV CA. An emerging consensus is that a conserved TRIM5α-binding mode exists for various viral capsids and that the surface details of the CA lattice dictate the species-specific interaction with TRIM5α (5,14,22,(41)(42)(43). On the other hand, TRIM5α possesses an intriguing curvature-independent pattern-recognition property.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a six nucleotide insertion/deletion polymorphism in the V1 region of rhesus macaque TRIM5α (TFP339Q in Fig. 5) is sufficient to explain differential restriction of HIV-2 (Wilson et al 2008a) and SIVagmTAN (Newman and Johnson, unpub-lished results) by the most common rhTRIM5α alleles, but it is not clear whether this is due to the small difference in length or amino acid composition (or both). Similarly, a 20 amino acid duplication found in an African green monkey TRIM5α ortholog transfers the capacity to restrict SIVmac239 when reconstituted in the context of human TRIM5α (Nakayama et al 2005).…”
Section: Trim5 Sequence Evolutionmentioning
confidence: 99%
“…A number of independent studies have examined polymorphisms in rhesus macaques and identified alleles that exhibit significant differences in their ability to restrict diverse retroviruses. [75][76][77][78] One of these studies, by Lim and colleagues, observed significant differences in the ability of different TRIM5a alleles present in these macaques to inhibit infection by SIVmac239, a viral strain commonly used to infect rhesus macaques to induce an AIDS-like disease in studies of AIDS pathogenesis and vaccine strategies. [79][80][81] Critically, not only did intraspecies allelic differences affect restriction of SIVmac239 in single cycle infectivity assays, these differences also conferred altered susceptibility to critical aspects of AIDS-like disease progression, including peak and set-point plasma RNA levels, CD4 T cell depletion, and survival.…”
Section: The Emerging Relationship Between Capsid Recognition Domainsmentioning
confidence: 99%
“…In humans, the majority of polymorphisms occur within the RBCC motif in regions of the protein that are not thought to be responsible for modulating TRIM5a specificity to individual retroviruses. [70][71][72]74 Conversely, almost all of the nonsynonymous SNPs identified in rhesus macaques are located in the SPRY and CC domains, [75][76][77][78] which are the regions of the protein reported to dictate the specificity of TRIM5a restriction (Fig. 2).…”
Section: The Emerging Relationship Between Capsid Recognition Domainsmentioning
confidence: 99%